-(w+5)+2w-11=-27

Simple and best practice solution for -(w+5)+2w-11=-27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(w+5)+2w-11=-27 equation:


Simplifying
-1(w + 5) + 2w + -11 = -27

Reorder the terms:
-1(5 + w) + 2w + -11 = -27
(5 * -1 + w * -1) + 2w + -11 = -27
(-5 + -1w) + 2w + -11 = -27

Reorder the terms:
-5 + -11 + -1w + 2w = -27

Combine like terms: -5 + -11 = -16
-16 + -1w + 2w = -27

Combine like terms: -1w + 2w = 1w
-16 + 1w = -27

Solving
-16 + 1w = -27

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '16' to each side of the equation.
-16 + 16 + 1w = -27 + 16

Combine like terms: -16 + 16 = 0
0 + 1w = -27 + 16
1w = -27 + 16

Combine like terms: -27 + 16 = -11
1w = -11

Divide each side by '1'.
w = -11

Simplifying
w = -11

See similar equations:

| 4z+2z=5z-3 | | d(t)=360-60t | | 7y+15=4y-6 | | x^2+y^2-8x+2y+8=0 | | 2n-3(5)=n-2(7) | | 2n-3(5)=7(n-2) | | 6(X-4)=32-2x | | 4*1/2−2*2/3= | | -4/3s=7/9 | | 5x-1.5=9c+3 | | 4z-9z=32 | | 30.25+x=35 | | 4x1/2−2x2/3= | | 2x(3)=5(x-1) | | 3(z+8)-2z=23 | | 8x+4=11x+10 | | 3x+5.39=-4.58 | | (-3x^3/y^2)^2 | | x-10x-1=0 | | 9-4x=-5x+5 | | 8d=9d-18 | | 7x=2+3x+6x | | 4t+8=68 | | -4.1+8.4=9s-5.3-8s | | 11-2x+12=15 | | 7n=2+3x+6x | | 9.6=17s | | 4x-10+5x=8x+3x+2 | | 8x=-7x | | -2=19-x | | 8-2x-6-12x=4 | | 12+5x=7(x-1) |

Equations solver categories